Upaya Meningkatkan Hasil Belajar Peserta Didik Menggunakan Model Contextual Teaching And Learning (CTL) Pada Materi Segi Banyak Beraturan Dan Lingkaran Kelas V SD Negeri Tambakreja 05 Cilacap Selatan - Perintis Vindi Ahadiyah; Sri Muryaningsih (Journal on Education, 2024)
This research was motivated by the low learning outcomes of students, aiming to determine the improvement in student learning outcomes using the Contextual Teaching and Learning (CTL) model on the topic of regular polygons and circles. It is a Classroom Action Research (CAR). The subjects of the research were 30 students of Grade V at SDN Tambakreja 05, Cilacap Selatan. The research consisted of two cycles, each cycle comprising two meetings. Data collection techniques included tests, interviews, observations, and documentation. The indicator of success for this research was that 80% of students achieved a Minimum Mastery Criterion (KKTP) score of 68. The results of the research showed that the improvement in student learning outcomes using the Contextual Teaching and Learning (CTL) model was evident from the students' enthusiasm in receiving the lessons and their confidence in directly practicing the material they had learned. Based on the research findings, the students' average learning achievement score was 70.04 in the first cycle and 80.27 in the second cycle. Classical completeness in the first cycle reached 52.51% with the criterion of 'less' and in the second cycle reached 87.03% with the criterion of 'very good'. In conclusion, the Contextual Teaching and Learning (CTL) model can improve student learning outcomes on the material of regular polygons and circles in Grade V of SDN Tambakreja 05, Cilacap Selatan.